O processo de internacionalização da cidade de Marília: um estudo a partir das empresas exportadoras - Souza, Daniel Elias de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
At the end of the twentieth century, processes and policies intensified the phenomenon of globalization. Thus, trade relations between developed countries and countries that are still under development now offer new characteristics of unequal relations. In this context, there was also a process of change in the internal dynamics between poles well integrated into the international market, such as global cities and more inland regions. It was then sought to understand how a medium-sized city like Marília, which stands out nationally and regionally as an industrial food center, was inserted in the paradigms of the financial globalization, seeking to elucidate how the process of integration of the exporting companies in the municipality occurred in the commercial activities of international character. For this, the activities sought to understand which are the most predominant exporting companies, which have the use of direct or indirect exportation and which types of companies or markets are most used in the commercial relations of the companies in the municipality. As a way to obtain information on the issues raised, a process of data collection was done with the use of interviews with managers from the companies in the municipality, with the use of data available in official databases and in a bibliographic survey for theoretical interpretation of the data. It was concluded that the city of Marília was inserted in a higher way in the international market from the second half of the 1990s, when its industrial companies began to actively export. In addition, it is worth noting the importance of the Latin American market for these companies, as well as the performance of non-industrial companies, especially a trading company.

No fim do século XX, ocorreram processos econômicos e políticos que intensificaram o fenômeno da globalização financeira. Assim, as relações comerciais entre países centrais e periféricos passaram a apresentar novas características de manutenção de relações desiguais. Nesse contexto, houve também um processo de alteração nas dinâmicas internas entre polos bem integrados ao mercado internacional como cidades globais e regiões mais interioranas. Buscou-se então compreender como uma cidade média como Marília, a qual se destaca regional e nacionalmente como um polo industrial alimentício, inseriu-se nesses paradigmas da globalização financeira, buscando elucidar como ocorreu o processo de integração das empresas exportadoras do município nas atividades comerciais de caráter internacional. Para isso, procurou-se compreender quais empresas exportam, quais os tipos de empresas mais predominantes, se há o uso de exportação direta ou indireta, quais os mercados mais utilizados nas relações comerciais das empresas do município e se há a atividade de trading companies ou empresas industriais no município. Como forma de obter dados e informações a respeito das questões levantadas, foi realizado um processo de levantamento de dados com base em visitas a empresas de Marília, em buscas por informações em bancos de dados oficiais e em levantamento bibliográfico para interpretação teórica dos dados obtidos. Concluiu-se então que a cidade de Marília se inseriu de forma mais elevada no mercado internacional a partir da segunda metade da década de 1990, época em que suas empresas industriais passaram a exportar ativamente. Além disso, cabe destacar a importância do mercado latino americano para essas empresas, assim como a atuação de empresas não industriais, em especial uma trading company.
The process of internationalization of the city of Marília: a study on the exporting companies
Keywords: Trading company; Economic internationalization; City of Marília; Exporting companies; Internacionalização econômica; Cidade de Marília; Empresas exportadoras